Pengembangan E-Modul Menggunakan Aplikasi Book Creator Berbasis Problem Based Learning Materi Bentuk Aljabar - Nuraini; Hartatiana; Wardani, Ambarsari Kusuma (Eksponen, 2024)
Development (R&D) research using research procedures using the ADDIE development model which includes five stages (Analysis, Design, Development, Implementation and Evaluation). Data collection techniques in this study used interviews, questionnaires, and tests. The subjects of the study were students of grade VII SMP N 44 Palembang. The results of this study show that valid E-Modules are seen based on the assessment of validation questionnaire sheets from validators obtained that the developed e-modules are declared very valid with a validity percentage of 88.26%. Practical E-Modules are seen based on the assessment of student response questionnaires, it is found that the e-modules developed are declared very practical with a percentage of practicality of 85.76%. An effective E-Module can be seen from the results of students' answers to the learning outcomes test with the percentage of student learning outcomes tests reaching 81.6% which is included in the very good category.